Principal's Strategy in Learning Management During the Covid-19 Pandemic at Samarinda State Vocational School - Harliansyah, Harliansyah (Educationist: Journal of Educational and Cultural Studies, 2022)
This study aims to describe: (1) planning, (2) implementing, (3) evaluating the principal's strategy in learning management during the Covid-19 pandemic. This research was conducted at SMK Negeri Samarinda using a qualitative approach with the case method. Data collection techniques through interviews, observation, and documentation. Data analysis begins with the stages of data reduction, drawing conclusions and verification, and presenting data. The results of this study indicate that the principal's strategy in planning learning during the Covid-19 pandemic is; designing IT-based learning strategies, preparing facilities and infrastructure, empowering teacher human resources in the IT field, and budget allocation. The school principal's strategy in implementing learning during the Covid-19 pandemic, namely; communication (in the form of meetings and telecommunications in the Whatsapp Group), lesson plans (in the form of IT-based learning media), and motivation. The principal's strategy in learning evaluation is carried out during the learning process and at the end, followed by monitoring at any time.